Srbska postmoderna proza na koncu 20. stoletja - Damjanov, Sava (Slavistična revija, 2002)
The article discusses the prelevant prose models and poetics in Serbian prose at he turn of the 20th c., presetnts the leading authors and their narrative methods.
Keywords: 1980/2000; intertekstualnost; Intertextuality; postmodernizem; srbska književnost; srbska proza